2008
DOI: 10.1016/j.ecolecon.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

What triggers environmental management and innovation? Empirical evidence for Germany

Abstract: Bibliografische Information Der Deutschen Bibliothek AbstractIt is frequently hypothesized that environmental management systems (EMSs) may improve a firm's environmental performance. Whether or not this hypothesis is true is as important from the perspective of environmental policy as questions relating to the relevant incentives for (1) a firm's voluntary adoption of an EMS and (2) its environmental innovation behavior. Based on ample empirical evidence for German manufacturing, this paper addresses these is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(137 citation statements)
references
References 10 publications
2
111
0
6
Order By: Relevance
“…It therefore follows that sustainability practices and leadership in green technology innovation are also less likely to be found in the developing world, as a wide body of literature has portrayed the link between environmental regulation and innovation behavior in environmental technologies (Porter 1991;Norberg-Bohm 1999;Frondel et al 2004). Furthermore, as the two largest coal producing and consuming countries in the developing world, China and India may represent the least likely places in which renewable energy technology industries might be expected to thrive.…”
Section: Case Selection and Data Collectionmentioning
confidence: 98%
“…It therefore follows that sustainability practices and leadership in green technology innovation are also less likely to be found in the developing world, as a wide body of literature has portrayed the link between environmental regulation and innovation behavior in environmental technologies (Porter 1991;Norberg-Bohm 1999;Frondel et al 2004). Furthermore, as the two largest coal producing and consuming countries in the developing world, China and India may represent the least likely places in which renewable energy technology industries might be expected to thrive.…”
Section: Case Selection and Data Collectionmentioning
confidence: 98%
“…Another factor is the financial burden that comes along with the implementation of an EMS. For example, studies about the situation in China, Germany, Japan and Singapore (Zeng et al, 2003;Frondel et al, 2008;Nakamura et al, 2001;Quazi et al, 2001, respectively) all find that costs are a disincentive in the adoption decision. However, they only refer to total costs associated with EMS adoption.…”
Section: Literaturementioning
confidence: 95%
“…Almost all studies on environmental management system implementation and environmental certification use samples of large companies (Mir and Feitelson, 2007;Mir, 2008; an example is Rai et al, 2010). In this perspective, the most important incentives appear to be the need to comply with legal requirements (Biondi et al, 2000;Quazi et al, 2001;Yiridoe et al 2003), public relations (Biondi et al, 2000;Zeng et al, 2003;Brody et al, 2006), environmental awareness (Nakamura et al, 2001), creating goodwill (Khanna and Anton, 2002), competitive position (Biondi et al, 2000;Zeng et al, 2003) and employee motivation (Frondel et al, 2008). Many companies succumb in the face of social pressure and care about their image.…”
Section: Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Existing research has shown that a firm's decision to introduce eco-innovations is influenced by a variety of factors, including regulation (as the "regulatory push/pull effect"), technology push, market pull (e.g., the concept of customer benefits), policy (changing laws), and firm-specific aspects (such as knowledge transfer mechanisms and involvement in networks) [39][40][41][42][43][44]. Based on these studies we consider the following three drivers as highly relevant for the adoption of eco-innovations: market pull (measured by "perceived need for action"); regulation (measured by "regulation awareness"); and firm-specific aspects (measured by "knowledge on eco-innovation" and "markets pull" or "technology push").…”
Section: Introductionmentioning
confidence: 99%